Brg1 and RUNX1 synergy in regulating TRPM4 channel in mouse cardiomyocytes - Ban, Tao; Dong, Xianhui; Ma, Ziyue; Jin, Jing; Li, Jing; Cui, Yunfeng; Fu, Yuyang; Wang, Yongzhen; Xue, Yadong; Tong, Tingting; Zhang, Kai; Han, Yuxuan; et al. (Frontiers in Pharmacology, 2024)
Transient Receptor Potential Melastatin 4 (TRPM4), a non-selective cation channel, is pivotal in cardiac conduction anomalies. The chromatin remodeler Brg1, known for its ATP-dependent modulation of nucleosome architecture, significantly influences gene expression regulation, impacting both heart development and disease pathogenesis. Our previous investigations have highlighted Brg1's role in modulating cardiac sodium channels and enhancing electrophysiological stability, its effect on TRPM4 expression and function has not been delineated. In this study , we found overexpression and knockdown Brg1 could positive-regulate TRPM4 expression in mouse cardiomyocytes. Brg1 also modulated TRPM4 current in TRPM4-overexpressed HEK293 cells. Notably, Brg1 inhibition markedly diminishes TRPM4's hyperexpression in cardiomyocytes exposed to hypoxia. Integrative analyses utilizing STRNG databases and Protein Data Bank unveiled a putative interaction between Brg1 and the transcription factor RUNX1, and the interaction between Brg1 and RUNX1 was substantiated through Co-immunoprecipitation. The binding sites of RUNX1 with the TRPM4 promoter region was predicted by the JASPAR database, and empirical validation through dual luciferase reporter assays and Chromatin Immunoprecipitation (ChIP) substantiated Brg1 modulated TRPM4 promoter activity via RUNX1 engagement. Collectively, our findings revealed BRG1 and RUNX1 formed a transcription complex, which modulated the transcription activity of TRPM4, thereby influencing TRPM4 expression and function, underscoring its therapeutic potential in cardiac hypoxia.